The Role of Physical Exercise During Chemotherapy in Women with Breast Cancer: A Narrative Review - Niewęgłowska, Małgorzata; Krazińska , Oliwia; Bernad, Mateusz; Widomska, Katarzyna; Bender, Aleksandra; Walczak, Paulina; Szymulewicz, Bartłomiej; Dąbrowski, Kacper; Łukaszewicz , Jakub; Gałach, Magdalena (Quality in Sport, 2026)
Background. Breast cancer is the most frequently diagnosed malignancy in women worldwide. Advances in oncologic therapy have markedly improved survival, yet chemotherapy and other treatments produce adverse effects such as fatigue, cancer‑related cognitive impairment, and reduced quality of life. Aim. To synthesize recent evidence on the impact of structured exercise interventions on physical fitness, cognitive function, and health‑related quality of life (HRQOL) in women undergoing or recovering from breast‑cancer treatment. Methods. A structured literature search of PubMed, PEDro, and Scopus identified English‑language studies published in the past ten years that evaluated exercise programs in adult women receiving or having completed chemotherapy. Trials were screened for outcomes related to cardiorespiratory fitness, muscle strength, fatigue, cognition and HRQOL as well as biological mechanisms and limitations. Results. The majority of randomized controlled trials reported that supervised aerobic, resistance, or combined exercise programs significantly attenuated fatigue and enhanced HRQOL (Ficarra et al., 2022). Meta‑analyses confirm a small but reliable improvement in cognitive function across diverse exercise modalities (Hung et al., 2025). Exercise also produced clinically meaningful gains in cardiorespiratory fitness, muscle strength, and shoulder range of motion, while being safe with few serious adverse events. Conclusions. Structured, supervised exercise initiated early during chemotherapy is safe and yields consistent benefits in physical fitness, cognition, and HRQOL for women with breast cancer. Standardized protocols and larger, high‑quality RCTs are needed to refine dosage guidelines and elucidate underlying molecular mechanisms.